1987
DOI: 10.1029/rg025i006p01376
|View full text |Cite
|
Sign up to set email alerts
|

Ocean chemical fluxes 1983–1986

Abstract: This review covers U.S. contributions in marine chemistry 1983–1986 in the areas of nutrient chemistry, carbon cycle, trace elements, oxygen cycling, radioisotopes (natural and artificial), particles and primary productivity. In most cases a simple review of important trends in this very large and diverse literature set is all that can be considered. The literature explosion in these areas results in more than 350 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 310 publications
0
3
0
Order By: Relevance
“…The term "pelagic" sediment was coined by Murray and Renard [1884, 1891] to designate those sediments which accumulate on the ocean floor by settling through the water column. Originally, it was assumed that the particles settled separately through the water, but more recently it has become evident that most particles settle in aggregates, usually as fecal pellets [Honjo, 1977;Brewer and Glover, 1987]. In addition to the pelagic sediment proper, the ocean floor receives "terrigenous" sediments [Murray and Renard, 1884, 1891] from land or island sources, which arrive directly at the bottom of the ocean without settling.…”
mentioning
confidence: 92%
“…The term "pelagic" sediment was coined by Murray and Renard [1884, 1891] to designate those sediments which accumulate on the ocean floor by settling through the water column. Originally, it was assumed that the particles settled separately through the water, but more recently it has become evident that most particles settle in aggregates, usually as fecal pellets [Honjo, 1977;Brewer and Glover, 1987]. In addition to the pelagic sediment proper, the ocean floor receives "terrigenous" sediments [Murray and Renard, 1884, 1891] from land or island sources, which arrive directly at the bottom of the ocean without settling.…”
mentioning
confidence: 92%
“…Contaminants in gaseous and particulate phases are delivered through the atmosphere to the open ocean from continental and coastal environments or may come directly from ship traffic (20)(21)(22). The mesopelagic zone of the water column, between 250 and 1500 m depth, receives a transient flux of contaminants associated with particulate matter from the surface (23). However, most particles pass through the midwater, and sorption properties favor retention of hydrophobic contaminants on particles (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…This was • noted by Bruland (1983) in his review on elemental concentrations in sea water, who observed: "The decrease of three orders of magnitude in the accepted concentration of lead in sea-water over the past four decades is not a real effect but is an artifact of successive improvements in reduction and control of the level of contamination introduced during sampling, storage and analysis." Subsequent reviews have contained similar observations (e.g., Brewer and Glover, 1987). All of them acknowledge that the first accurate measurements of lead concentrations in the ocean were made with samples collected from the North Pacific in 1976-1977(Schaule and Patterson, 1981) and the North Atlantic in 1979(Schaule and Patterson, 1983.…”
mentioning
confidence: 89%